Plan de Marketing para la Empresa Constructora Quispe Soto S.A., ubicado, en el cantón Zapotillo provincia de Loja - Soto Carrión, Ronald Fabricio (2017)
The present investigation was carried out in the company Constructor QUISPE SOTO SA, located in the "Zapotillo Canton," province of Loja, whose purpose is to contribute in its organizational development, since during its operating time, it has not been elaborated Or executed a marketing plan, which does not allow a business development to increase its sales and publicity, to have a better positioning and participation in the market, to look for the different strategies that allow to give alternatives of solution to the problems that appear within the Company and in this way strengthen its image and quality of service. In the results we present the interpretation of each of the analyzes, PESTEC matrix study of political, economic, social and cultural, technological and competitive factors, allowed to find key information for the company in such results found can be determined in the Matrix MEFE that gives a weighted result a value of 2.80 which means that the company has good opportunities such as: subsidies policy that favor the construction companies, technological innovation that helps to achieve better results and that the investment is less, access To mortgage loans of $ 40,000 and $ 70,000 that they apply for the purchase of finished homes, an increase in the population growth rate of 2.65%, which is a determining factor of the sector's growing behavior and among its threats are involution in the state's general budget Which reduces investments to carry out works or to give subsidies by the government Tariff legislation that raises the price of inputs and machinery has a surcharge of 5 to 45%, inflation at 1.78% is negative as the purchasing power of customers remains low. When conducting the competitive analysis allowed to know the main competitors, such as Constructor Rosario Santa Fe occupying a position of 3.24 leads the market, secondly the Constructor Quispe Soto in a position of 2.48 defining aspects in which it is At a disadvantage as quality of personnel in the sales department, thirdly the Constructor Oderbreach with a position of 2.01. 6 The internal analysis resulted in a 2.90 which indicates that the constructor has more strengths than weaknesses; Where strengths weigh more as they are, good market coverage, optimum machinery and adequate tools; Likewise, its most important weaknesses were identified as the lack of market research, lack of publicity and there is no training for sales staff. The market investigation was then carried out to identify and solve the various problems that may be encountered by the company, determined that 93.33% of clients state that they are satisfied with the services they have received Of the construction company because they provide confidence and security, 93% indicate that prices are accessible, 90% say they have not been favored by promotions. Once all the analysis and market research was completed, the SWOT matrix was created, which allowed the creation of a list of strategies FO, FA, DA, DO according to the compatibility of internal and external factors; The proposal of a marketing plan for Constructor Quispe Soto S.A. Where there is a proposal of business philosophy, policies to fulfill the plan, growth opportunities, the results allowed to clearly define four strategic objectives of the plan, which are: Increase the sales of the construction company by 20% by the year 2018. A quality service to the clients, so that the loyalty of them is achieved. Develop a training plan that improves the work performance of staff, providing better service to customers. Increase the market share by 30% by the construction. Finally, after the studies carried out, it has been concluded that the construction company Quispe Soto has important opportunities such as: subsidy policy that favors the construction companies, technological innovation help to achieve better results and that the investment is lower, increase of the Rate of Population growth 2.65% which is a determining factor of the sector's growing behavior, development of communications that allow the customer to know and market quickly and its main threats such as the law of safeguards implanted in the country and the high level of unemployment , The recommendations for the construction company are: to be aware of the changes that may occur in the environment, taking into account the threats and opportunities, 7 improve the aspects in which it is at a significant disadvantage, such as increasing the number of sales staff, Motivate them and enable them to improve their competitive profile, Take advantage of the existing strengths to minimize the weaknesses that the constructor has, implementing improvement strategies with the purpose of increasing their sales and achieving better profitis